Implementasi Sistem Informasi Pemesanan Jasa Desain 3D Berbasis Website - Abrar, Achmad Khairil; Pratiwi, Nunik (Jutisi : Jurnal Ilmiah Teknik Informatika dan Sistem Informasi, 2024)
AZero Creative is a business in the field of 3D design modeling services which currently has problems recording and managing order data. Recording orders placed transfers the order data client from direct message Instagram the microsoft excel which can result in incomplete and inaccurate data. The aim of this research is to produce an information system for ordering 3D design services that can make it easier to record and manage data as well as create reports. The research method produced in building this 3D design service ordering information system uses Extreme Programming. Test result black box, this information system is in accordance with needs and desires user and test results system usability scale obtained a SUS score of 77.18. The score of this information system is included in the category grade B and adjective rating great. This states that this information system is suitable for use by AZero Creative to assist in recording and managing data as well as creating reports.Keywords: Information Systems; Services; 3D Design; Extreme Programming; System Usability ScaleÂ AbstrakAZero Creative adalah bisnis dalam bidang jasa modelling desain 3D yang saat ini kendalanya pencatatan dan pengelolaan data pesanan. Pencatatan pesanan yang dilakukan mentransfer data pesanan client dari direct message Instagram ke microsoft excel yang dapat mengakibatkan data kurang lengkap dan tidak akurat. Tujuan penelitian ini menghasilkan sistem informasi pemesanan jasa desain 3D yang dapat mempermudah dalam pencatatan dan pengelolaan data serta pembuatan laporan. Metode penelitian yang dihasilkan dalam membangun sistem informasi pemesanan jasa desain 3D ini menggunakan Extreme Programming. Hasil Pengujian blackbox, sistem informasi ini sesuai dengan kebutuhan dan keinginan user dan hasil pengujian system usability scale memperoleh skor SUS 77,18. Skor tersebut sistem informasi ini masuk dalam kategori grade B dan adjective rating great. Hal tersebut menyatakan bahwa sistem informasi ini layak digunakan AZero Creative untuk membantu dalam hal pencatatan dan pengelolaan data serta pembuatan laporan.Â